The role of offset in the enduring gestation of Indonesia’s strategic industries - Maharani, Curie; Matthews, Ron (Taylor & Francis, 2023)
The purpose of this paper is to examine the performance of Indonesia’s informal offset policy over the period 1976-2014. The paper offers four original academic perspectives: firstly, it is framed by reference to what Indonesia’s former Minister of Technology, Dr Habibie, described as the Progressive Manufacturing Plan, a novel approach in which offset was intended to play a critical supportive role in the systematic development of strategic civil-military industries; secondly, the analysis is structured into three distinctive ‘development-survival-revival’ industrialisation stages that impacted on the performance of both offset and the broader defence economy; thirdly, the study is uniquely different in the sense that the offset case studies all occurred in an era absent of a formal offset policy regime; and lastly, the study provides a wealth of rich data in a subject field well-known for its sensitivity, if not secrecy, and thus is characterised by a paucity of empirical evaluation.
Keywords: Indonesia; defence offset; defence industry; strategic industries